EMOTION REGULATION STRATEGIES IN HADITH PERSPECTIVE AND THEIR RELEVANCE TO CONTEMPORARY PSYCHOLOGY - Eriska Razilhija; Romlah Abubakar Askar; Abdul Ghofur (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to examine emotion regulation strategies from the perspective of Hadith and their relevance to contemporary psychology. The main focus of this research is on three Hadiths that provide guidance on managing emotions, particularly anger: Hadith Abu Dawud no. 4150 on reciting ta'awudz when angry, Hadith Abu Dawud no. 4151 on changing body posture when angry, and Hadith Isnad Shahih no. 9630 on the prohibition of anger. These three Hadiths teach techniques that can help individuals manage their emotions effectively, such as seeking protection from Allah, changing physical conditions to relieve tension, and restraining from anger. From the perspective of contemporary psychology, these strategies resemble emotion regulation approaches found in theories such as cognitive reappraisal and emotion regulation strategies, which aim to change perception or physiological responses to negative emotions. This research also reveals how teachings in the Hadith can be used as a foundation to understand emotion regulation more holistically, integrating both spiritual and psychological dimensions. Through this understanding, the study highlights the importance of integrating Islamic teachings with contemporary psychological principles to create a more comprehensive approach to managing human emotions, particularly anger, in the modern world.